OMBUDSMAN: SUATU KAJIAN ANALISIS - Yeni Sri Lestari (Universitas Teuku Umar, 2016)
This article analyzes the history and role of the Ombudsman in improving the quality of public service delivery by government officials of a country. The establishment of the Ombudsman is an important step that is done to balance the performance of the apparatus of government in providing public services and justice to the people. This study is important as a reference many countries are working to improve the quality of public services personnel administration. Therefore, the discussion in this article is what is meant by the Ombudsman? How Ombudsman formed? The second is how the performance of the Ombudsman? And how is the impact of the Ombudsman? This study found that the background of the establishment of Ombudsman first appeared in Sweden is based on the Swedish government's efforts to create a balance of public services by government officials and the general public to the demands of globalization and democracy today. At the end of the study it was found that by taking a study on the Ombudsman parliamentary in New Zealand and the United Kingdom found that the practice of the concept of Ombudsman institutions have a positive impact to the management of the public service, it then becomes the impetus for other countries to participate in establishing the Ombudsman.Keywords: Ombudsman, New Zealand, United Kingdom